(untitled) (SAARC Journal of Agriculture, 2023)
This study aims to understand how climate change affects livestock production in Bangladesh from 1971 to 2020 and its economic impacts. Different econometric tests, such as unit root tests, Johansen cointegration test, and the fully modified OLS (FMOLS) method, are used to conduct the study. The findings show that livestock production is negatively impacted by higher temperatures, increased precipitation, and greenhouse gas emissions. Greenhouse gas emissions leads to global warming and increase the mortality rate of livestock. Additionally, higher temperatures result in decreased metabolism, reduced feed intake, and increased heat stress. Excessive rainfall creates a damp and humid environment, leading to various diseases. On the other hand, lower temperatures and flood-affected areas have positive effects on livestock production. Warmer minimum temperatures improve water quality, reduce diseases and parasites, and enhance the breeding success of livestock. Floods provide increased water availability, sediments, nutrients, and more grassland. The economic influences caused by climate change in the livestock sector are massive. This has adverse effects on farms’ profitability, employment rates, income, insurance expenses, production costs, and demand-pull inflation. Notably, from 2009 to 2020, the livestock industry suffers substantial economic losses due to climate change. To mitigate climate change’s impact on livestock production in Bangladesh, implementing improved livestock management techniques, efficient water systems, resilient animal breeds, and alternative feed sources is crucial. Collaborative efforts between policymakers, agricultural institutions, and international organizations are essential to encouraging farmers to adopt climate-smart practices. SAARC J. Agric., 21(2): 227-238 (2023)